2007
DOI: 10.1364/oe.15.012654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of optical correction and remaining aberrations on peripheral resolution acuity in the human eye

Abstract: Retinal sampling poses a fundamental limit to resolution acuity in the periphery. However, reduced image quality from optical aberrations may also influence peripheral resolution. In this study, we investigate the impact of different degrees of optical correction on acuity in the periphery. We used an adaptive optics system to measure and modify the off-axis aberrations of the right eye of six normal subjects at 20 degrees eccentricity. The system consists of a Hartmann-Shack sensor, a deformable mirror, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…Information on these peripheral aberrations is of interest for research on, for example, the effect of optical errors on peripheral vision [8][9][10][11], improving vision for people with central vision field loss [12,13], and eye modeling with individual data retrieved from ocular wavefront tomography [14,15]. Furthermore, the interest in measurements of peripheral refractive errors has increased, due to their possible link to myopia [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Information on these peripheral aberrations is of interest for research on, for example, the effect of optical errors on peripheral vision [8][9][10][11], improving vision for people with central vision field loss [12,13], and eye modeling with individual data retrieved from ocular wavefront tomography [14,15]. Furthermore, the interest in measurements of peripheral refractive errors has increased, due to their possible link to myopia [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One study (Lundström et al 2007) has shown that in the periphery, the optics of the eye do not limit grating resolution. Or, equivalently, visual acuity in the periphery could not be improved with optical corrections.…”
Section: Image Quality In the Peripheral Retinamentioning
confidence: 99%
“…Artal et al, 2010; Atchison et al, 2009a Atchison et al, , 2009bde Gracia et al, 2010;Elliott et al, 2009;Gupta et al, 2010;Lundstrom et al, 2007;Marcos et al, 2008;Perez et al, 2009;Rocha et al, 2007Rocha et al, , 2010Rossi and Roorda, 2010;Rossi et al, 2007;Rouger et al, 2009;Sawides et al, 2010;Williams et al, 2000;Yoon & Williams, 2002). Adaptive optics can be used to study visual performance by generating specific novel aberration patterns in the eye (e.g.…”
Section: Adaptive Optics For Vision Correctionmentioning
confidence: 99%